The Influence of Music Therapy and Mindfulness Meditation in Reducing Anxiety in Elderly Individuals Undergoing Hemodialysis: A Systemic Review - Aminah Soemadi Al Djuwardi; Etty Rekawati; Dikha Ayu Kurnia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Approximately 40-50% of hemodialysis patients are elderly who experience chronic health conditions such as end-stage renal disease. Routine medications, lifestyle changes, and side effects of treatment often cause anxiety. Anxiety is described as a disturbing feeling as a situation of fear or threat. The sensation of anxiety can consist of palpitations, tremors, nervousness, and shortness of breath, interfering with the procedure. hemodialysis. Long duration of treatment and physical discomfort caused by it cause anxiety. Therefore, appropriate and safe non-pharmacological therapy is needed in the elderly. Objective to reduce anxiety in the elderly undergoing hemodialysis. The search was conducted through journal sources from ScienceDirect, ProQuest, EBSCO, and Pubmed (2019-2024) with keywords using medical subject headings (MeSH)